Fulfillment of Patient Expectations After Spine Surgery is Critical to Patient Satisfaction: A Cohort Study of Spine Surgery Patients. Issue 1 (22nd July 2022) - Rampersaud, Y. Raja; Canizares, Mayilee; Perruccio, Anthony V.; Abraham, Edward; Bailey, Christopher S.; Christie, Sean D.; Evaniew, Nathan; Finkelstein, Joel A.; Glennie, Raymond Andrew; Johnson, Michael G.; Nataraj, Andrew; Paquet, Jerome; et al.
Abstract : BACKGROUND: Patient satisfaction is an important indicator used to monitor quality of care and outcomes after spine surgery. OBJECTIVE: To examine the complex relationship between preoperative expectations, fulfillment of expectations, postsurgical outcomes, and satisfaction after spine surgery. METHODS: In this national study of patients undergoing elective surgery for degenerative spinal conditions from the Canadian Spine Outcomes and Research Network Registry, we used logistic regression to examine the relationships between patient satisfaction with surgery (1-5 scale), preoperative expectation score (0 = none to 100 = highest), fulfillment of expectations, and disability and pain improvement. RESULTS: Fifty-eight percent of patients were extremely satisfied, and 3% were extremely dissatisfied. Expectations were variable and generally high (mean 79.5 of 100) while 17.3% reported that none of their expectations were met, 49.8% reported that their most important expectation was met, and 32.9% reported that their most important expectation was not met but others were. The results from the fully adjusted ordinal logistic model for satisfaction indicate that satisfaction was higher among patients with higher preoperative expectations (odds ratio [OR] [95% CI]: 1.11, [1.04-1.19]), reporting important improvements in disability (OR [95% CI]: 2.52 [1.96-3.25]) and pain (OR [95% CI]: 1.64 [1.25-2.15]) and reporting that expectations were fulfilled (OR = 80.15, for all expectations were met). The results were similar for lumbar and cervical patients. CONCLUSION: Given the dominant impact of expectation fulfillment on satisfaction level, there is an opportunity for improving overall patient satisfaction by specifically assessing and mitigating the potential discrepancies between patients' preoperative expectations and likely surgical outcomes. The findings are likely relevant across elective surgical populations.